MEMPERTIMBANGKAN TINGKAT MAQASID ASY-SYAHRI???AH DALAM PENETUAN ANGGARAN BELANJA PEMERINTAH (EVALUASI TERHADAP APBN 2008-2013) - Hidayani (Program Studi Perbankan Syariah, 2019)
This paper is the result of a study evaluating three things, namely: how to position maqasid ash-Shari'ah in the perspective of Islamic economy, how to determine the state budget according to the perspective of maqasid ash-Shari'ah, and how to distribute the state budget based on the perspective of maqasid ash-Shari'ah. Of the three issues were then further clarified about the ideas and basic principles of Islamic economy related to the maqasid ash-Shari'ah. In addition, the approach also addressed the value associated with the state budget in the system of Islamic economy. Furthermore, the concepts of Islamic economy on the state budget that can be applied in real life were discussed. To obtain the data, three methodological frameworks in Islamic economy were used. They consist of the idea and the basic principles of Islamic economy, Islamic value approach towards the conditions of Islamic economy, and the concept of Islamic economy that can be derived in real conditions. It can be concluded that at first the state budget should be based on five aspects:the maintenance of religion, life, lineage, sense and treasure. Second, according to maqasid ash-Shari'ah by using domain analysis and looking at the realization of state budget in 2008 ??? 2013, the budget did not describe the level of the existing maqasid ash-Shari'ah or in the moderate level. It can be seen from the hierarchy pooling of maqasid ash-Shari'ah that the maintainance of life (hifdzuan-nafs)ranks first with a total budget of Rp.137.4 trillion;followed by the maintenance oftreasure(hifdzu al-mal) with a total budget of 122.9 trillion; maintenance of sense (hifdzu al-aql) with a total budget of121 trillion; maintenance of religion(hifdzu ad-din)with a total budget of 40.6 trillion;and maintenance of lineage(hifdzuan-nasl)with a total budget of 12.4 trillion.